ADAPTASI TIGA VARIETAS PEPAYA (MERAH DELIMA, JUPE, MADU) DI LAHAN KERING DATARAN RENDAH - Muhammad Anang Firmansyah; Teguh Pribadi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2019)
Papaya fruit (Carica papaya L.) is  classified as having high economic value and is being developed by many farmer.  A common problem is the papaya variety that farmer \s develop usually from careless seeds, so the production and quality are low.  The aim of this research is to introduce superior papaya and have good quality. Three varieties papaya are used in this study, namely: Merah Delima, Jupe, and Madu.The research location is located in the dry land of Banturung, Palangka Raya City.  The result that the land suitability class of the study site included S3wa,on, which is Marginal Suitability with the heaviest inhibiting factors of water availability and oxygen availability. On Growth parameters, then Merah Delima has the largest stem circumference  of 10,1 cm althought it is not significantly different from other varieties 8,8 cm.  While the plant height is the best Merah Delima  papaya and signficantly different from Madu. Interms of Productioan Jupe has a number of Fruits (38 fruits/tree) that are significantly different from Madu, and the weight of fruit (1,2 kg/fruit) is significantly different from Merah Delima., and fruit weight per tree 34,1 kg is significantly different from the other two varieties.  Base on the sweetness level, the sweetest Merah Delima reaches 9,1 oBrix significantly different from Jupe (6,9 oBrix) and Madu (6,6 oBrix).  Parameters of growth, productionand quality of papaya can still be improved by improving the management of inhibiting factors.